Conducting a multi‐country online alcohol survey in the time of the COVID‐19 pandemic: Opportunities and challenges. Issue 3 (5th May 2021) - Kilian, Carolin; Rehm, Jürgen; Allebeck, Peter; Barták, Miroslav; Braddick, Fleur; Gual, Antoni; Matrai, Silvia; Petruželka, Benjamin; Rogalewicz, Vladimir; Rossow, Ingeborg; Schulte, Bernd; Štelemėkas, Mindaugas; et al.
Abstract: Objectives: This contribution provides insights into the methodology of a pan‐European population‐based online survey, performed without external funding during the COVID‐19 pandemic. We present the impact of different dissemination strategies to collect data from a non‐probabilistic convenience sample and outline post‐stratification weighting schemes, to provide guidance for future multi‐country survey studies. Methods: Description and comparison of dissemination strategies for five exemplary countries (Czechia, Germany, Lithuania, Norway, Spain) participating in the Alcohol Use and COVID‐19 Survey. Comparison of the sample distribution with the country's actual population distribution according to sociodemographics, and development of weighting schemes. Results: The dissemination of online surveys through national newspapers, paid social media adverts and dissemination with the support of national health ministries turned out to be the most effective strategies. Monitoring the responses and adapting dissemination strategies to reach under‐represented groups, and the application of sample weights were helpful to achieve an analytic sample matching the respective general population profiles. Conclusion: Reaching a large pan‐European convenience sample, including most European countries, in a short time was feasible, with the support of a broad scientific network.